Pengembangan Sistem Informasi Pengadaan Buku Perpustakaan untuk Meningkatkan Efisiensi dan Transparansi Manajemen Koleksi - Ariani, Linda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This study aims to develop and implement a Library Book Procurement Information System to enhance the efficiency and transparency of collection management in libraries. The system is designed to automate and streamline the processes involved in book procurement, from requisition and approval to acquisition and cataloging. Key features include a user-friendly interface for book requests, automated approval workflows, vendor management, budget tracking, and real-time updates on procurement status. By integrating advanced data management and real-time communication technologies, the system ensures accurate and timely procurement of books, reducing delays and errors. The research discusses the design, development, and deployment phases of the system, including the selection of appropriate technologies, system architecture, and user interface design. The system is evaluated based on its impact on operational efficiency, transparency in the procurement process, and user satisfaction. The results indicate that the implementation of the Library Book Procurement Information System leads to significant improvements in the efficiency of book acquisition, enhances accountability, and ensures better allocation of library resources. The paper also addresses the challenges encountered during the development and deployment phases, as well as the solutions implemented to overcome these challenges.